Effect of Attapulgite Nanorods and Calcium Sulfate Microwhiskers on the Reaction-Induced Phase Separation of Epoxy/PES Blends. (4th August 2013) - Tang, Xiaolin; Zhong, Xinhui; Zhan, Guozhu; Yu, Yingfeng; Zhang, Hongdong
Abstract : The influence of two kinds of mesoscale inorganic rod fillers, nanoscale attapulgite and micron-sized CaSO4 whisker, on the reaction-induced phase separation of epoxy/aromatic amine/poly- (ether sulfone) (PES) blends has been investigated by optical microscopy (OM), scanning electron microscopy (SEM), and time resolved light scattering (TRLS). By varying the PES concentration and curing temperature, we found that the incorporation of attapulgite and CaSO4 had dramatic impact on the phase separation process and the final phase morphology of blends. In blends at higher content than critical concentration, the process of phase separation was retarded by the incorporation of nanoscale fillers but accelerated by that of the micron-sized fillers, mainly due to the enhanced viscoelastic effect and the preferential wettable effect, respectively. Meanwhile both mesoscale fillers could change the cocontinuous phase structure of blends with lower PES content than critical concentration into PES-rich dispersed structure due to the surface affinity of fillers to epoxy matrix.